2018
DOI: 10.1002/int.21995
|View full text |Cite
|
Sign up to set email alerts
|

Generating Z-number based on OWA weights using maximum entropy

Abstract: In the application of Z‐number, how to generate Z‐number is a significant and open issue. In this paper, we proposed a method of generating Z‐number based on the OWA weights using maximum entropy considering the attitude (preference) of the decision maker. Some numerical examples are used to illustrate the effectiveness of the proposed method. Results show that the attitude (preference) of the decision maker can give an optimal possibility distribution of the reliability for Z‐number using maximum entropy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 79 publications
(45 citation statements)
references
References 36 publications
0
45
0
Order By: Relevance
“…Many math tools are presented to model uncertainty, such as Z numbers, [53][54][55] D numbers, [56][57][58][59][60][61] and entropy model. [62][63][64][65][66][67] Among then, evidence theory is widely used due to its efficiency to deal with uncertainty.…”
Section: Preliminariesmentioning
confidence: 99%
“…Many math tools are presented to model uncertainty, such as Z numbers, [53][54][55] D numbers, [56][57][58][59][60][61] and entropy model. [62][63][64][65][66][67] Among then, evidence theory is widely used due to its efficiency to deal with uncertainty.…”
Section: Preliminariesmentioning
confidence: 99%
“…Fuzzy logic was developed by Zadeh and Mamdani and Assilian, based on which the concept of approximate reasoning was introduced and showed that vague logical statements enable the formation of algorithms that can use vague data to derive vague inferences. Many theories have been promoted by this method, such as Dempster‐Shafer theory, Z‐numbers, and fuzzy reasoning . The definition of fuzzy sets is given as follows:…”
Section: Fuzzy Sets and Ivfssmentioning
confidence: 99%
“…Fuzzy logic was developed by Zadeh 26 and Mamdani and Assilian, 27 based on which the concept of approximate reasoning was introduced and showed that vague logical statements enable the formation of algorithms that can use vague data to derive vague inferences. Many theories have been promoted by this method, such as Dempster-Shafer theory, [28][29][30][31] Z-numbers, [32][33][34] and fuzzy reasoning. [35][36][37] The definition of fuzzy sets is given as follows: Note that the membership function can take any value from the closed interval [0, 1], and the greater μ x ( ) A is, the greater the truth of the statement that element x belongs to set A is.…”
Section: Fuzzy Sets and Ivfssmentioning
confidence: 99%
“…Clearly, using expressions (23) and (25), we can obtain directly the optimal weights given a specified degree of orness Ω by first computing the Lagrange multiplier λ 2 from Equation (25) and then by computing the Lagrange multiplier λ 1 from (22), thus solving the constrained optimization problem in (8)-(9).…”
Section: Filev and Yager's Analytic Construction Of Meowa Weightsmentioning
confidence: 99%
“…Applications of the maximum entropy approach can be found in various fields, see, for instance, Chang et al, Liaw et al, Yusoff and Merigó‐Lindahl, Chuu, He et al, and Kang et al. Two very recent applications of the maximum entropy method are described in Kim and Ahn and Brunelli and Fedrizzi.…”
Section: Introductionmentioning
confidence: 99%